Use of the pictet-spengler reaction for the synthesis of 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines and 1,4-disubstituted-beta-carbolines: formation of gamma-carbolines - Kusurkar, Radhika S.; Alkobati, Nabil A. H.; Gokule, Anita S.; Puranik, Vedavati G. (Tetrahedron, 2008)
Microwave-assisted conjugate addition of indole on nitro-olefins furnished nitro compounds, which were reduced to tryptamines. Further, by using Pictet-Spengler condensation, new 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines were synthesized in diastereoselective manner. Dehydrogenation of the tetrahydro-beta-carbolines produced new 1,4-disubstituted-beta-carbolines. As a new observation, in some of the cases, Pictet-Spengler condensation and dehydrogenation gave two products, namely 1,4-disubstituted-beta-carbolines and 1,4-disubstituted-gamma-carbolines. A mechanism is proposed for this observation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3; 4-Disubstituted-1; 4-disubstituted-beta-carboline; 4-disubstituted-gamma-carboline; 4-tetrahydro-beta-carboline; 4-tetrahydro-gamma-carboline; Pictet-Spengler reaction

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction